Updating Vocational English Textbooks to Meet Industrial Demands in Indonesia - Pohan, Albert Efendi; Harahap, Dahrul Aman; Hasibuan, Juli Rachmadani; Ghani, Muhammad Faizal A.; Alsamiri, Yasir Ayed; Sari, Hartika; Beni, Ramdhan; Ashari, Erwin (JOLLT Journal of Languages and Language Teaching, 2025)
The pressing demand for work-relevant vocational English textbooks is essential for delivering effective learning materials that align with students' requirements. Appropriate textbooks can boost English language competence by enhancing students' abilities in listening, speaking, reading, and writing. Listening skills form the cornerstone for developing proficiency in other language areas. However, survey revealed that 92.3% of the 52 vocational schools in Batam City had not updated their English textbooks, and 96.2% lacked listening materials tailored to industrial demands. As a result, only 11.87% of the 4,035 Batam City vocational school students who passed the test showed competence in the listening component of the English assessment. This research aims to create a valid and effective vocational English textbook that improves students' English communication abilities based on workplace requirements. To accomplish this goal, the study employed a developmental research approach (Borg and Gall). The research was conducted in Batam City, encompassing 52 vocational schools, 95 English teachers, and 4,070 vocational school students in Batam City, Indonesia. The study's outcomes indicate that: 1) the vocational English listening textbook developed was empirically validated with an average score of 3.6, placing it in the highly valid category. 2) This textbook has also been empirically shown to be effective in enhancing students' listening competence, with a sig. value of 0.000, which was below 0.05. Consequently, this textbook benefits the government and stakeholders, particularly vocational English instructors in Batam City, by improving their English communication competence through the provision of textbooks relevant to industrial contexts.